2015
DOI: 10.1021/acs.energyfuels.5b02316
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Pyrolysis of Used Engine Oil over Coal Ash into Fuel-like Products

Abstract: The present paper reports on the conversion of spent lubricating oil (SLO) into useful fuel-like products through two-stage pyrolysis. Liquid pyrolysates (LPs) from the first stage were obtained using prebaked clay (PBC) as adsorbent and subjected to second stage pyrolysis over coal ash (CA) as catalyst. The PBC and CA were characterized by using morphological, elemental, surface, and crystallographic properties. The influence of CA concentration on the yield of LPs and their compositions in terms of hydrocarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
3
13
0
3
Order By: Relevance
“…The results of FTIR analysis also revealed that the spectrum bands related to the oils were predominantly similar to both that of commercial diesel fuel [15] and those of other catalytic oils obtained from the catalytic cracking of the waste transformer oil with the use of a catalyst such as fly ash [6] and hydroquinone [16]. Furthermore, the comparative spectra belong to the oils of TO and BCTO was in agreement with those of other studies [17,18] containing the used engine oil and the spent lubricant engine oil with the use of a catalyst of coal ash and barium-strontium ferrite.…”
Section: Effect Of Bentonite On the Chemical Composition Of Liquid Prsupporting
confidence: 87%
“…The results of FTIR analysis also revealed that the spectrum bands related to the oils were predominantly similar to both that of commercial diesel fuel [15] and those of other catalytic oils obtained from the catalytic cracking of the waste transformer oil with the use of a catalyst such as fly ash [6] and hydroquinone [16]. Furthermore, the comparative spectra belong to the oils of TO and BCTO was in agreement with those of other studies [17,18] containing the used engine oil and the spent lubricant engine oil with the use of a catalyst of coal ash and barium-strontium ferrite.…”
Section: Effect Of Bentonite On the Chemical Composition Of Liquid Prsupporting
confidence: 87%
“…The relative distribution of different carbon range hydrocarbons in the CDLP is given in Table 8. As we reported earlier, 28 the relative distributions of C 6 −C 12 , C 13 −C 16 , C 17 −C 20 , C 21 −C 30 , and >C 30 range hydrocarbons were observed to be 62.7, 16.95, 9.32, 6.77 and 3.38%, respectively in case of the thermal run wherein the proportion of different carbon range hydrocarbons linearly decreased as their molecular weights increased. The result of the catalyzed run shows no obvious difference with the thermal run.…”
Section: Ft-ir Analysissupporting
confidence: 80%
“…It can be observed that CDLP consists of individual hydrocarbons with minor differences in their relative concentrations, as determined in the case of the thermal run. 28 The paraffinic hydrocarbons identified included heptane, 3-ethyl-2,4-dimethylpentane, octane, nonane, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, heptadecane, octadecane, nonadecane, eicosane, henicosane, docosane, tetracosane, and pentacosane and their alkyl derivatives. The concentrations of most of the individual compounds ranged from 1 wt% to as high as 6 wt%.…”
Section: Individual Compoundsmentioning
confidence: 99%
“…The composition of Al-Fe-rich particles was similar to that of oil and coal fly ash emitted from local sources such as oil-and coal-fired boilers ( Figure 5), and similar in composition to oil and coal ash as reported in the scientific literature [66][67][68][69][70][71][72][73]. This makes it possible to use these values as source diagnostic ratios for source apportionment, regardless of study area location.…”
Section: Chemical Composition Of Potential Source Emissionssupporting
confidence: 73%